Preliminary study on processing of liquid waste using a sequencing batch reactor at a model scale (The effect of aeration) - Maspanger Dadi R (Proceedings : Indonesian Rubber Conference and IRRDB symposiun 2000 Indonesian Rubber Research Institute, Bogor, Indonesia, 12-14 September 2000.V.II.pp.308-313.)
Competition among rubber producing countries, regulations on environmental aspects such as clean production program, ecolabelling, and ISO 14000, have forced crumb rubber factories to improve their production process including the handling of their liquid waste.. In this research a study on liquid waste using SBR ( sequencing batch reactor) in a model scale had been conducted. The experiments were done in Sukamaju Estate of PTP Nusantara VII starting July until December 1999. The result showed that SBR is a liquid waste handling system, which could reduce land use. The liquid effluent used in this experiment has parameters as follows: BOD 398-450mg/L, COD 797-898 mg/L, Total Solid Suspended 328-367 mg/L, N-NH3 21-35 mg/L, N-total 44-56 mg/L and pH 5,5-6,5. Using two model scale of SBR reactors with a volume of 25 m3 and 4m deep, the optimum result was obtained at effluent debit of 2-2, 5m3, 10-12 hours refilling, aeration airflow of 8-1 L/second, blower 5 kW, sedimentation period 8-12 jam and 2 hours decantation. The result is TSS 47-95 m/L, BOD 114 mg/L, COD 138-188 mg/L, N-NH3 3-4,6 mg/L, N-total 6, 8-9,7 and pH 6,0-7,0. These parameters are still in the standard requirements of effluent quality according to the letter from Minister of Environment Number MenLH No.51/MENLH/10/1995 valid during the year 2000. The advantage of SBR use is the need of land is minimum, easily to be applied on crumb rubber factories located in cities with limited land use. This study needs further experiments on the use SBR in commercial scale in the production line of crumb rubberfactories.
Keywords: Batch reactor; Liquid waste processing; Sequencing